Pharmacologic reactivation of latent feline immunodeficiency virus ex vivo in peripheral CD4+ T-lymphocytes - McDonnel, Samantha J. (2012)
FIV establishes a latent infection in peripheral CD4+ T-cells, and the latent FIV promoter is associated with deacetylated, methylated histones, consistent with a restrictive chromatin structure. Here we explored the use of 5 histone-modifying agents - 4 histone deacetylase inhibitors (HDACi) and 1 histone methyltransferase inhibitor (HMTi) - to reactivate latent FIV ex vivo. All compounds tested were able to alter histone lysine residue modifications in feline cells, both globally and at the FIV promoter locally. When latently FIV-infected peripheral CD4+ T-cells were cultured ex vivo in the presence of these inhibitors, viral transcription was significantly activated relative to no treatment controls. Transcriptional reactivation of virus mediated by the HDACi suberoylanilide hydroxamic acid (SAHA) was dose-dependent, detected after as little as 1 hour of exposure, and resulted in virion formation as evidenced by supernatant reverse transcriptase activity. A synergistic effect was not found when SAHA was combined with HMTi under the conditions tested. At low therapeutically relevant concentrations in primary feline PBMC, SAHA was found to be minimally cytotoxic and non-immune activating. HDACi and HMTi can reactivate latent FIV ex vivo, and SAHA, also known as the anticancer drug Vorinostat, in particular is a promising candidate for in vivo use because of its efficacy, potency, and relative safety. Use of the FIV/cat model of lentiviral latency to explore in vivo treatment with SAHA and other anti-latency therapeutics will allow investigations that are either ethically or logistically not addressable in patients persistently infected with human immunodeficiency virus (HIV-1).